Measuring Global Poverty - Wisor, S. author. aut Link
XIII, 241 p.
Keywords: The author examines the moral, methodological, and practical problems that arise from poverty measurement. He establishes a methodological framework for analyzing poverty conceptions and measures, and concludes with concrete recommendations regarding both the procedures for and substance of future global poverty measurement.